ANALISA EBIT-EPS TERHADAP STRUKTUR MODAL OPTIMAL PADA PT SEMEN INDONESIA (PERSERO) Tbk - Rahayu, Runik Puji (JURNAL AKUNTANSI DAN INVESTASI, 2016)
One of the problems in the capital is how to set the optimal capital structure for the company, because the capital structure is a balance between foreign capital and the capital itself. The effectiveness of capital structure will determine whether or not the efficiency of the use of funds given the level of EBIT-EPS that the company had achieved. Currently, PT Semen Indonesia (Persero) Tbk has the optimal capital structure with 27.1% the proportion of debt and equity capital of 72.9%. The purpose of this study was to determine how the EBIT-EPS analysis of the optimal capital structure of the company for five years (2010-2014) using quantitative descriptive research method with a kind of case study at PT Semen Indonesia (Persero) Tbk through the analysis process EPS, EBIT analysis -EPS to determine the optimal capital structure. The results showed that the optimal capital structure in PT Semen Indonesia (Persero) Tbk occurred in 2014. This is evidenced by the size of the acquisition EBIT amounted to Rp 7,155,668,037 and net profit of Rp 5,565,857,595 so that EPS has increased as high as Rp 938. Based on the EBIT-EPS approach the company in expanding Preferred Shares should use alternative because it will obtain a high EPS. Therefore, companies also need to consider in the selection of an optimal capital structure that will generate the highest value of EPS